2019
DOI: 10.1002/2211-5463.12677
|View full text |Cite
|
Sign up to set email alerts
|

BAG6 deficiency induces mis‐distribution of mitochondrial clusters under depolarization

Abstract: Accumulation of damaged mitochondria is implicated in a number of neurodegenerative disorders, including Parkinson's disease. Therefore, the machinery for mitochondrial quality control is important for the prevention of such diseases. It has been reported that Parkin‐ and p62/sequestosome 1 (SQSTM1)‐mediated clustering and subsequent elimination of damaged mitochondria (termed mitophagy) are critical for maintaining the quality of mitochondria under stress induced by uncoupling agents such as carbonyl cyanide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…44 Particularly, the deficiency of BAG6 can reduce the mitochondria size, lead to the mis-distribution of mitochondrial clusters under depolarization, induce activation of the PINK1/PARKIN pathway and the phospho-ubiquitination of mitochondrial proteins, which abrogates the ability to induce mitophagy. 46,47 As an excellent regulator of autophagy, BAG6 plays an important role in the response of organisms to stress. 48 For instance, BAG6 is required for plant defense against pathogens and tolerance to abiotic stresses, and plays a key role in coordinating neurotranscriptomic changes in the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“…44 Particularly, the deficiency of BAG6 can reduce the mitochondria size, lead to the mis-distribution of mitochondrial clusters under depolarization, induce activation of the PINK1/PARKIN pathway and the phospho-ubiquitination of mitochondrial proteins, which abrogates the ability to induce mitophagy. 46,47 As an excellent regulator of autophagy, BAG6 plays an important role in the response of organisms to stress. 48 For instance, BAG6 is required for plant defense against pathogens and tolerance to abiotic stresses, and plays a key role in coordinating neurotranscriptomic changes in the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“…8,25 It is also established that BAG6 is important for the cytoplasmic redistribution of damaged mitochondria in a PARKIN-dependent manner. 19 Interestingly, other BAG family members are also involved in PINK1/PARKIN signaling and mitochondrial quality control. BAG2 stabilizes PINK1 by decreasing its ubiquitination and allowing mitophagy induction.…”
Section: Discussionmentioning
confidence: 99%
“…18 BAG6 is also involved in the PARKIN-dependent cytoplasmic redistribution of damaged mitochondria. 19 In this work, we investigated BAG6 role in the regulation of mitophagy after mitochondrial depolarization. We first demonstrated that BAG6 is present in the mitochondria of all the tested cell lines (SW480, MEFs, HEK293T, and in BAG6transfected null cells LoVo).…”
Section: Introductionmentioning
confidence: 99%
“…Bag6 acts as a co-chaperone, negatively regulating HSP70's protein folding capacity (29), in opposition to BAG2 and BAG5. BAG6 acts to target misfolded proteins for proteasomal degradation (62), regulates the distribution of damaged mitochondria (63), and stabilizes the apoptosis inducing factor (AIF) (64), which has been implicated in MPP+ toxicity (65). BAG6 knockout neurons are resistant to ER-stress induced cell death (66).…”
Section: Discussionmentioning
confidence: 99%